Endoscopy and minimally invasive surgery in the diagnosis and treatment of precancerous diseases and cancer of the stomach in the early stages - Bondarenko, I. N.; Mashtaler, V. Ye.; Barannikov, K. V.; Chebanov, K. O.; Prokhach, A. V.; Dmitrenko, E. A. (Морфологія / Morphologia / Morfologìâ, 2016)
One of the most urgent problems of modern oncology is cancer of the stomach, which takes one of the leading places in the structure of cancer incidence. Given the high prevalence of gastric cancer and aggressive course of the disease it is extremely necessary to solve the problem of early diagnosis based on evidence-based medicine and meticulously comply with this disease screening protocols. The review highlights the main precancerous processes and conditions prior to the appearance of tumor, especially degeneration of precancerous lesions to cancer. In particular, to precancerous conditions include chronic atrophic gastritis, pernicious anemia, intestinal metaplasia of the gastric epithelium, the appearance of polyps, endured surgery on the stomach, Menetries disease. These diseases with different frequencies give rise to different degrees of severity of dysplasia, and metaplasia of the stomach epithelium, and ultimately cancer. Understanding precancerous states helps to shape risk and carefully carry out the selection of patients for screening activities to develop the tactics of treatment of precancer and early gastric cancer. The standard diagnosis is endoscopy, which allows to perform a biopsy of the alleged pathological focus for subsequent histological examination is necessary for morphological verification of diagnosis and patient management. To improve the method used technique of chromoesdoscopic examination. Thanks to the introduction of new technologies into clinical practice, such as particular zoom magnification endoscopy, endoscopic examination in a narrow spectral range, endoscopic ultrasound, has become possible to more accurately determine the boundaries of the tumor, depth of invasion into the stomach wall and correctly assess the state of the regional lymph nodes. Diagnosis of early forms of gastric cancer has opened opportunities for sparing endoscopic interventions, namely endoscopic mucosal resection of the stomach, endoscopic submucosal dissection by layer, photodynamic therapy and laser destruction. All these techniques can improve patient survival and quality of life by improving the methods for early diagnosis of the disease and organ sparing surgery.